PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KERIPIK SINGKONG PEDAS (Studi Kasus Pada Dona Home Industry Food and Snack di Baturaja) - Anisa Wahida; Rosmala Dewi; Nourma Wulanda (Ekonomika, 2025)
This study discusses the Influence of Product Quality (X1), and Price (X2) on Purchase Decisions (Y) a case study on Dona home food and snack industry in Baturaja. The population in this study is consumers who shop directly at the Dona home industry food and snack store in Baturaja which totals 88 people. This study is quantitative research with the analysis method used, namely Multiple Linear Regression Analysis which uses Validity and Reliability Tests. The results of the analysis show that Product Quality and Price Variables affect Purchase Decisions both partially and simultaneously. The coefficient of determination (R2) was obtained as 0.595. This shows that the contribution of Product Quality (X1) and Price (X2) to the Purchase Decision (Y) of the Product is 59.5% while the remaining 40.5% is influenced by other variables that are not included in this model such as promotion, distribution channel (Kotler, P., & Keller, 2016).